Threat Factors and Prevention Strategies for Computer Network Security - Bai, Lijie (Journal of Artificial Intelligence and Information, 2025)
With the rapid development of Internet technology, computer network has become an indispensable part of modern society. Computer networks play a crucial role in personal life, business operations, and national management. However, with the popularization of network applications, network security issues have become increasingly prominent and have become an important factor restricting the development of computer networks. Therefore, strengthening research on network security technology during the operation of computer systems, analyzing influencing factors, and timely preventing and controlling related risks are of great significance for ensuring the effective application of computer network technology.